2021
DOI: 10.26434/chemrxiv.14595654.v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Label-Free Plasmonic Biosensor for Rapid, Quantitative, and Highly Sensitive COVID-19 Serology: Implementation and Clinical Validation

Abstract: Serological tests are essential for the control and management of COVID-19 pandemic, not only for current and historical diagnostics but especially for surveillance, epidemiological, and acquired immunity studies. Clinical COVID-19 serology is routinely performed by enzymatic or chemiluminescence immunoassays (i.e., ELISA or CLIA), which provide good sensitivities at the expense of relatively long turnaround times and specialized laboratory settings. Rapid serological tests, based on lateral flow assays, have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Different types of biosensors developed in the laboratory for COVID‐19 are represents in Table 2. [ 46,48,65,78‐86,87,88 ]…”
Section: Examples Of Developed Biosensors For Covid‐19 Detectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of biosensors developed in the laboratory for COVID‐19 are represents in Table 2. [ 46,48,65,78‐86,87,88 ]…”
Section: Examples Of Developed Biosensors For Covid‐19 Detectionmentioning
confidence: 99%
“…Spiked saliva 90 fM 10-30 s [79] Electrochemical immunosensor Antigens Saliva 19 ng/ml and 8 ng/ml 30 min [80] Multiplexed grating-coupled fluorescent plasmonics biosensor Antigens Serum and dried blood 30 min [81] Field effect transistor (FET)based biosensor Antigen Swab 2.42 Â 10 2 copies/ml - [82] Electrochemical biosensor Antibody Serum 0.96 (IgG) and 0.14 ng/ml (IgM)…”
Section: Antigensmentioning
confidence: 99%
“…41 Another study also demonstrated the performance of SPR for screening antibodies on 120 samples pre-characterized using standard regulatory-approved commercial detection kits available at time of collection. 42 Building on these studies, we applied a rapid BSL-2 "pseudoneutralization" assay 18 to measure the binding inhibition between the viral spike protein and ACE-2 receptor in over 1000 serum samples collected during a 18 month period in a cohort of food and retail workers. The data collected with SPR sensors were validated using a live virus microneutralization assay (BSL-3), the current gold standard assay for SARS-CoV-2-specific antibody, and captured the changes in the humoral response that were consistent with the timescale of vaccination campaigns and SARS-CoV-2 outbreaks.…”
Section: Introductionmentioning
confidence: 99%